Early switch to oral anticoagulation in patients with acute intermediate-risk pulmonary embolism (PEITHO-2): a multinational, multicentre, single-arm, phase 4 trial. Issue 9 (September 2021) - Klok, Frederikus A; Toenges, Gerrit; Mavromanoli, Anna C; Barco, Stefano; Ageno, Walter; Bouvaist, Hélène; Brodmann, Marianne; Cuccia, Claudio; Couturaud, Francis; Dellas, Claudia; Dimopoulos, Konstantinos; Duerschmied, Daniel; et al.
Summary: Background: Current guidelines recommend a risk-adjusted treatment strategy for the management of acute pulmonary embolism. This is a particular patient category for whom optimal treatment (anticoagulant treatment, reperfusion strategies, and duration of hospitalisation) is currently unknown. We investigated whether treatment of acute intermediate-risk pulmonary embolism with parenteral anticoagulation for a short period of 72 h, followed by a switch to a direct oral anticoagulant (dabigatran), is effective and safe. Methods: We did a multinational, multicentre, single-arm, phase 4 trial at 42 hospitals in Austria, Belgium, France, Germany, Italy, Netherlands, Romania, Slovenia, and Spain. Adult patients (aged ≥18 years) with symptomatic intermediate-risk pulmonary embolism, with or without deep-vein thrombosis, were enrolled. Patients received parenteral low-molecular-weight or unfractionated heparin for 72 h after diagnosis of pulmonary embolism before switching to oral dabigatran 150 mg twice per day following a standard clinical assessment. The primary outcome was recurrent symptomatic venous thromboembolism or pulmonary embolism-related death within 6 months. The primary and safety outcomes were assessed in the intention-to-treat population. The study was terminated early, as advised by the data safety and monitoring board, following sample size adaptation after the predefined interim analysis on Dec 18, 2018. This trial is registered with the EU Clinical Trials Register (EudraCT 2015-001830-12) and ClinicalTrials.gov (NCT02596555 ). Findings: Between Jan 1, 2016, and July 31, 2019, 1418 patients with pulmonary embolism were screened, of whom 402 were enrolled and were included in the intention-to-treat analysis (median age was 69·5 years [IQR 60·0–78·0); 192 [48%] were women and 210 [52%] were men). Median follow-up was 217 days (IQR 210–224) and 370 (92%) patients adhered to the protocol. The primary outcome occurred in seven (2% [upper bound of right-sided 95% CI 3]; p<0·0001 for rejecting the null hypothesis) patients, with all events occurring in those with intermediate-high-risk pulmonary embolism (seven [3%; upper bound of right-sided 95% CI 5] of 283). At 6 months, 11 (3% [95% CI 1–5]) of 402 patients had at least one major bleeding event and 16 (4% [2–6]) had at least one clinically relevant non-major bleeding event; the only fatal haemorrhage occurred in one (<1%) patient before the switch to dabigatran. Interpretation: A strategy of early switch from heparin to dabigatran following standard clinical assessment was effective and safe in patients with intermediate-risk pulmonary embolism. Our results can help to refine guideline recommendations for the initial treatment of acute intermediate-risk pulmonary embolism, optimising the use of resources and avoiding extended hospitalisation. Funding: German Federal Ministry of Education and Research, University Medical Center Mainz, and Boehringer Ingelheim.